Review of bamboo-feeding leafhopper genus Mukaria Distant (Hemiptera: Cicadellidae: Mukariinae) with description of a new species from China - Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2011)
The bamboo-feeding leafhopper genus Mukaria Distant is known to include eight species from China: M. albinotata Cai & Ge, M. bambusana Li & Chen, M. flavida Cai & Ge, M. lii sp. nov., M. maculata (Matsumura), M. nigra Kuoh & Kuoh, M. pallipes Li & Chen and M. testacea Chen, Liang & Li. One new species, M. lii sp. nov. (frp, Guizhou Province, China), is described and illustrated. A checklist of species, host plants and distribution of Mukaria are given along with a key to Chinese species.